Mechanistic Insight into the Enzymatic Reduction of Truncated Hemoglobin N of Mycobacterium tuberculosis: role of the CD loop and pre-A Motif in electron cycling - Singh, Sandeep (2014)
Background: The HbN of Mycobacterium tuberculosis carries a potent nitric-oxide dioxygenase activity despite lacking a reductase domain. Results: The NADH-ferredoxin reductase system acts as an efficient partner for the reduction of HbN. Conclusion: The interactions of HbN with the reductase are modulated by its CD loop and the Pre-A region. Significance: The present study provides new insights into the mechanism of electron transfer during nitric oxide detoxification by HbN.